Using quantitative methods for a student activity analysis in an online graduate course concerning their undergraduate education - Bago, Petra (Array, 2011)
In this paper we analyze the use of Moodle VLE by students who attended a fully online graduate-level course. Students were split up into two groups regarding their undergraduate education. The aim of this research is to determine if there is a significant difference between the two student groups concerning both time of assignment submission and number of resources and assignments (re)accessed. We conclude that no significant difference arises regarding time of assignment submission, but this appears with respect to the access to resources and assignments. Furthermore, there is a very low correlation between the time of assignment submission and: the final course scores, the number of resources and the number of assignments (re)accessed.